Factors related with length of stay (LOS) on digestive surgical patient in Dr. Wahidin Sudirohusodo hospital, Makassar, Indonesia - ., Warsinggih; Kasim, Nindy Agista; Harahap, Hidayah; Prihantono, Prihantono (International Journal of Research in Medical Sciences, 2018)
Background: Length of stay (LOS) is to show how many days a patient is admitted to the hospital during one treatment period. The best length of daycare is 6-9 days. Some factors affect the length of stay of the patient. This study aims to determine the factors associated with the duration of treatment on digestive surgical patients in Dr. Wahidin Sudirohusodo Hospital, Makassar, Indonesia. Methods: This research was analytical, descriptive research method using cross-sectional study design, and sampling used is total sampling technique with 419 patients. Data analysis was obtained to see the relationship between independent variables (sex, age, secondary diagnosis, surgery setting, surgery risk, and outcome) and the dependent variable (length of stay). Results: The study found that there were four factors related to the duration of treatment of digestive surgical patients that are secondary diagnosis (p = 0.000), surgery setting (p = 0.000), surgery risk (p = 0.000), and out patient condition (p = 0.000). While no significant relation the age with p value = 0.140, and sex p value = 0.917 with length of stay. Conclusions: There were four factors have a significant relationship with the length of stay (LOS) on a digestive surgical patient in dr. Wahidin Sudirohusodo Hospital such as secondary diagnosis, surgery setting, the risk of surgery and outpatient condition.